(untitled) (Research, Society and Development, 2022)
In This article aims to present and compare noise reduction techniques in the reconstruction of speech signals contaminated by colored noise in order to verify the spectral distortion generated by the processed signal. The discrete time and frequency Kalman filters in conjunction with the power spectral subtraction technique were used for noise reduction in signal reconstruction and compared. The signals used were contaminated by colored noise and the performance evaluation of the algorithms was performed using the segmented signal-to-noise ratio and the Itakura-Saito distance that verifies the spectral distortion in the processed signal. The best method found through the tests performed was the discrete time Kalman filter method together with the spectral power subtraction in relation to spectral distortion.